Help from my friends: cooperation of BMAL1 with noncircadian transcription factors - Shostak, Anton; Brunner, Michael (Genes & development, 2019)
The circadian clock in the suprachiasmatic nucleus (SCN) of mammals drives 24-h rhythms of sleep/wake cycles. Peripheral clocks present in other organs coordinate local and global physiology according to rhythmic signals from the SCN and via metabolic cues. The core circadian clockwork is identical in all cells. However, there is only a small amount of overlap of the circadian transcriptomes in different organs and tissues. A novel study by Beytebiere and colleagues (pp. 294-309) indicates that the regulation of tissue-specific rhythmic gene expression involves the cooperation of the circadian transcription factor (TF) BMAL1:CLOCK with tissue-specific TFs (ts-TFs) and correlates with the potential of BMAL1:CLOCK to facilitate rhythmic enhancer-enhancer interactions.
Gesehen am 27.03.2019